Partial Pulpotomy in Mature Permanent Molars with Symptoms Indicated Irreversible Pulpitis Using MTA: A Study of Three Case Reports over Four-Year Follow-Up - Rami Zenaldeen; Rami Kaddoura; Hasan Alzoubi; Hassan Achour; Ossama Aljabban (Case Reports in Dentistry)
VPT is vital pulp therapy, a biologically based procedure that combines several therapeutic techniques to maintain the entire or a portion of the dental pulp. Interest in VPT has grown due to recent developments in bioactive materials and an understanding of biological pulp reparative responses. This case report is aimed at evaluating the success rate of partial pulpotomy in permanent molars with symptoms indicating irreversible pulpitis using MTA and presenting with extremely deep carious lesions over four years of follow-up. All patients came with spontaneous and severe pain. Each tooth was isolated with a rubber dam and disinfected with 5.25% NaOCl before caries excavation. After caries removal, a partial pulpotomy was performed on 2–3 mm of the exposed pulp. Bleeding time was recorded after hemostasis was achieved, and then MTA was placed over the exposed pulp. The permanent restoration was placed after pulp capping, and postoperative periapical radiographs were taken. Patients were scheduled for clinical and radiological examinations for four years based on 6-month intervals. All teeth revealed a successful outcome throughout the follow-up periods (clinically and radiographically) with complete resolution of clinical signs and symptoms. Partial pulpotomy using MTA might be an effective long-term management strategy for permanent molars clinically diagnosed with irreversible pulpitis.